Characterization and modelling for copper cable attenuation and crosstalk up to 100MHz (High speed data bandwidth in copper cables) - NIK AHMAD FAIZUL, NIK SYAFINAZ SOFIA (2018)
The ability to provide stable connection in wired network introduces a higher demand to obtain greater bandwidth as compared to wireless technology. The new addition to the Digital subscriber line (DSL) family is known as Gigabyte fast access to terminal (G.fast) is expected to deliver data rates up to 1 Gbps up to distance of 250m. The maximum data rate that can be transported through copper cable is highly dependent on the characteristics of twisted pair cabling which are insertion loss and crosstalk coupling. In order for G.fast to become a commercial success, it is important to realistically characterize and model the channels between the last distribution point and the end-user premises equipment. This paper focuses on characterization and modelling for copper cable attenuation and crosstalk up to 350 Mhz. The motivation to study attenuation(IL) and crosstalk model is to come up with an accurate (Far end crosstalk) FEXT analysis and speed estimation. The cable insertion loss(IL) and FEXT are measured using 50 pairs twisted pair with diameter of 0.5mm at distance of 100m and 200m.The measurement involves a frequency range from 51.75Khz to 500Mhz and this range was selected to model measurement in G.fast environment. The result of this measurement was analysed after scattering parameters was extracted by using Agilent Technologies Network Analyser model E5071C.The results shows that there are differences in terms of characterization between 2 ports and 4 port measurement. The obtained IL and FEXT model is then verified using 99% worse case model and stochastic model against the actual measurement performed through lab testing.